(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the specific features of international advertising terminology, especially how it is expressed in French. It examines how terms and terms in the field of advertising change and develop depending on cultural, economic and social contexts. The article highlights the specificity of advertising terminology in French, its international acceptance and the problems in the translation process. It also discusses cultural differences in the process of creating advertising in French and their impact on advertising. This study provides useful information for professionals working in the field of advertising and highlights the importance of intercultural communication in the development of international advertising strategies.